用于超级电容器的NiSe-NiSe三维松叶状纳米材料及其制备方法 (2018)
本发明公开了种用作超级电容器的NiSe-NiSe三维松叶状纳米材料及其制备方法。该纳米材料由NiSe和NiSe两相组成，具有形貌结构均的三维松叶状纳米针形态，纳米针长度不、最长可达500nm，直径为5~25nm，用于电极其比电容值为970～1714F/g。NiSe-NiSe三维松叶状纳米材料采用步水热法合成，将四水合乙酸镍、亚硒酸钠先后溶于去离子水中，搅拌均匀后置于反应釜中，再加入水合肼和二乙烯三胺的混合液，将泡沫镍衬底浸入反应釜中，进行水热合成反应，即得到NiSe-NiSe三维松叶状纳米材料。本方法制备简单、节能环保，制得的产品电化学性能优异，适合工业化生产。 The invention discloses a NiSe-Ni3Se2 three-dimensional pine needle shaped nano material for a supercapacitor and a preparation method thereof. The nano material is composed of NiSe and Ni3Se2, has three-dimensional pine needle shaped nano-needles with a uniform morphologic structure, the nano-needles are varied in length, the maximum length can reach 500nm, the diameter is 5-25nm, and the specific capacitance of the nano-needles is 970-1714F/g when being applied to an electrode. The NiSe-Ni3Se2 three-dimensional pine needle shaped nano material is synthesized by adopting a one-step hydrothermal method, nickel acetate tetrahydrate and sodium selenite are successively dissolved into deionized water, the solution is uniformly stirr